Investigating the Effectiveness of Group Work in Mathematics - Anastasia Sofroniou (Education Sciences, 2016)
Group work permits students to develop a range of critical thinking, analytical and communication skills; effective team work; appreciation and respect for other views, techniques and problem-solving methods, all of which promote active learning and enhance student learning. This paper presents an evaluation of employing the didactic and pedagogical customs of group work in mathematics with the aim of improving student performance as well as exploring students’ perceptions of working in groups. The evaluation of group work was carried out during tutorial time with first year civil engineering students undertaking a mathematics module in their second semester. The aim was to investigate whether group work learning can help students gain a deeper understanding of the module content, develop improved critical and analytical thinking skills and see if this method of pedagogy can produce higher performance levels. The group work sessions were conducted over four weeks whilst studying the topic of integration. Evaluation surveys were collected at the end of the intervention along with an investigation into the examination results from the end of semester examinations. In order to derive plausible and reasonable conclusions, these examination results were compared with an analogous cohort of first year mathematics students, also studying integration in their engineering-based degree. The investigation into the effectiveness of group work showed interesting and encouraging positive outcomes, supported by a combination of qualitative and quantitative analysis.